Sinergi Kemitraan Universitas Riau dan Industri Rumah Tangga (IRT) Dalam Upaya Peningkatan Pendapatan dan Pengembangan Usaha - Sri Endang Kornita; Widia Edorita; Zamaya, Yelly; Selly Prima Desweni (Journal of Community Engagement Research for Sustainability, 2022)
The synergy of partnerships between Universitas Riau and business/industry actors in the region is important to be carried out in line with the tridharma of higher education at the point of community service. Among the industries and food businesses that are developing in the city of Pekanbaru, many of them are in the form of IRT which are still very simple in terms of capital, products produced, marketing methods and limited access to standardize their products. One of them is Rizky Nanda Home Industry, which has been running Bolu Kemojo. In order to be able to develop their business activities properly, and to be able to increase the income of the IRT, it is necessary to take steps and strategies for business development based on the conditions and problems faced. The method of application carried out in this service is assistance for IRT in branding and packaging as well as digital/online marketing of IRT products to improve product quality; foster business management skills in an effort to increase production capacity; and assistance in the legality of IRT products, as well as obtaining a Halal Certificate. In its implementation, this service activity involves 10 (ten) students participating in the 2021 Riau University Kukerta with community empowerment and mentoring programs that are integrated between the lecturer service program and work programs to be implemented. In the implementation of this service, the Kukerta team also accompanied IRT to decorate the appearance of the outlet to attract more buyers.